2007
DOI: 10.1177/1028315307299699
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and International Students: An Australian Study

Abstract: In a study of international student security, consisting of 200 intensive interviews with students, resident onshore in Australia, it was found that two thirds of the group had experienced problems of loneliness and/or isolation, especially in the early months. According to Weiss, students experience both personal loneliness because of the loss of contact with families and social loneliness because of the loss of networks. Both forms of loneliness are at times exacerbated by their experiences in institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
451
4
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 533 publications
(518 citation statements)
references
References 35 publications
17
451
4
15
Order By: Relevance
“…The difficulty that international students have in establishing contact with locals has been amply discussed in the literature (for example, Sawir, Marginson, Deumert, Nyland, & Ramia, 2008;Townsend & Poh, 2008). When asked about this, Angela attributed the difficulty to the fact that the locals were not particularly interested in foreign students who were only staying for a short time: locals, she argued, did not think it worth investing in them and trying to build friendships.…”
Section: Extract 1 Weekly Diary Table (English Translation)mentioning
confidence: 99%
“…The difficulty that international students have in establishing contact with locals has been amply discussed in the literature (for example, Sawir, Marginson, Deumert, Nyland, & Ramia, 2008;Townsend & Poh, 2008). When asked about this, Angela attributed the difficulty to the fact that the locals were not particularly interested in foreign students who were only staying for a short time: locals, she argued, did not think it worth investing in them and trying to build friendships.…”
Section: Extract 1 Weekly Diary Table (English Translation)mentioning
confidence: 99%
“…Em nosso estudo, tais desafios foram enfatizados pelos alunos brasileiros no exterior, o que eles percebem como falta de abertura por parte dos estudantes locais para formação de amizade e relacionamentos. Os relatos de dificuldades de socialização de alunos intercambistas com locais têm sido recorrentes na literatura (Mclachlan;Justice, 2009;Brown, 2009;Townsend;Poh, 2008;Sawir et al, 2008;Brunton, 2007), as quais têm sido usualmente associadas às barreiras do idioma e às diferenças nas normas culturais e na natureza das relações nos países anfitriões. As dificuldades de socialização com alunos locais têm sido associadas ao isolamento e à solidão, especialmente nos meses iniciais da mobilidade ( Sawir et al, 2008), o que também pudemos identificar em um caso relatado em nosso estudo.…”
Section: Discussão Sobre Os Desafios E Os Elementos Facilitadoresunclassified
“…Os relatos de dificuldades de socialização de alunos intercambistas com locais têm sido recorrentes na literatura (Mclachlan;Justice, 2009;Brown, 2009;Townsend;Poh, 2008;Sawir et al, 2008;Brunton, 2007), as quais têm sido usualmente associadas às barreiras do idioma e às diferenças nas normas culturais e na natureza das relações nos países anfitriões. As dificuldades de socialização com alunos locais têm sido associadas ao isolamento e à solidão, especialmente nos meses iniciais da mobilidade ( Sawir et al, 2008), o que também pudemos identificar em um caso relatado em nosso estudo. Por outro lado, os alunos estrangeiros no Brasil não relataram dificuldades de relacionamentos sociais dentro ou fora do contexto universitário, mas ao contrário, afirmam que as características do povo brasileiro favorecem a interação social, em razão de sua sociabilidade, sua abertura e seu interesse pelo estrangeiro.…”
Section: Discussão Sobre Os Desafios E Os Elementos Facilitadoresunclassified
“…Sawir et al [6] found that women reported loneliness more often than men in a sample of 200 university students in Australia. Graham and Juvonen [9] reported that adolescents of a minority ethnic group were found to report significantly (p<.001) more loneliness than majority adolescents in a study of 265 adolescents.…”
Section: Literature Review Lonelinessmentioning
confidence: 99%
“…Some studies showed that women report more loneliness than men [6], while other studies report more loneliness among men [7]. Persons of minority groups have also been found to report increased loneliness [8,9].…”
Section: Introductionmentioning
confidence: 99%